Value-based and benefit-based strategies in deciding to bring a test into use should be distinguished. Issue 1 (December 2017) - Vach, Werner
Abstract Background Regulatory and health technology assessment agencies have commented differently on the question whether results from enrichment studies can be used to justify to bring a test into use. We try to provide a framework to discuss this issue. Results Mathematical definitions for the value and the benefit of a new diagnostic test are given. The possible conclusions about value and benefit from enrichment studies and interaction studies are explored. The terms benefit-based strategy and value-based strategy are introduced. Several potential consequences of using one of the two strategies in deciding to bring a test into use are identified and quantified. Interaction designs allow to assess benefit and value. Enrichment designs allow only to assess benefit. However, it is often probable that interaction studies allow no firm conclusions about the value. The advantage of a benefit-based strategy stems mainly from allowing test-positive patients earlier or even ever to benefit. The main disadvantage is a potential delay in detecting tests of no value. Conclusions Benefit-based strategies are preferable if the risk of off-label use and of delayed decisions on the value of a test can be limited. Otherwise, the superiority depends highly on research practice.